2019
DOI: 10.1080/21691401.2019.1637881
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and potential mechanism of cnidium lactone to inhibit osteoclast differentiation

Abstract: Cnidium lactone is effective in the maintenance of bone mass in various osteoporosis models; however, the precise molecular mechanisms are not understood. In this study, we investigated the effects and underlying mechanisms of action of cnidium lactone on receptor activator of NF-jB ligand (RANKL)induced osteoclastogenesis. Cnidium lactone dose-dependently inhibited osteoclast differentiation and formation, decreased the bone-resorbing activity of osteoclasts, and downregulated the expression of osteoclast dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition, studies have shown that garcinol can reduce RANKL-induced osteoclastogenesis by regulating the PI3K/AKT/mTOR signaling pathway and the downstream factor c-FOS [ 40 ]. Cnidium lactone regulated osteoporosis by regulating c-FOS/NFATc1 signaling pathways through p38 MAPK and PI3K-Akt [ 41 ]. Further, we investigated its effect on MC3T3-E1 cells by overexpressing FOS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that garcinol can reduce RANKL-induced osteoclastogenesis by regulating the PI3K/AKT/mTOR signaling pathway and the downstream factor c-FOS [ 40 ]. Cnidium lactone regulated osteoporosis by regulating c-FOS/NFATc1 signaling pathways through p38 MAPK and PI3K-Akt [ 41 ]. Further, we investigated its effect on MC3T3-E1 cells by overexpressing FOS.…”
Section: Discussionmentioning
confidence: 99%
“…The murine macrophage cell line RAW 264.7 was used in the current study as it is widely used in osteoclastic experiments (Liang et al, 2019;Zeng et al, 2019). RAW 264.7 cells were obtained from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China).…”
Section: Cell Linesmentioning
confidence: 99%
“…Cnidium lactone is a potent herbal remedy that can prevent bone loss in a model of ovariectomyinduced bone loss in rats (Wang et al, 2020). Liang et al (2019) found in a study of RANKL-induced differentiation of RAW264.7 cells that Cnidium lactone could inhibit the differentiation of TRAP-positive multinucleated osteoclasts and reduce the bone resorption of osteoclasts. In molecular mechanism, Cnidium lactone is able to inhibit the expression of c-Fos and NFATc1, the main transcription factors of osteoclast differentiation, by inhibiting the levels of phosphorylation of p38 and AKT and reducing the expression of p38 MAPK and PI3K-Akt signaling pathways.…”
Section: Natural Plant Derivatives and Compounds Modulate The Akt Sig...mentioning
confidence: 99%